Targeting MDM2 affects spastin protein levels and functions: implications for HSP treatment - Francesca Sardina; Federica Polverino; Sonia Valentini; Claudia Carsetti; Elisabetta Falvo; Giada Tisci; Silvia Soddu; Fabiola Moretti; Alessandro Paiardini; Cinzia Rinaldo (Cell Death Discovery)
Abstract Spastin is a microtubule (MT) severing enzyme that regulates several cell functions associated with MT dynamics. A reduction in spastin protein levels is responsible for approximately 40% of cases of Hereditary Spastic Paraplegia (HSP), a neurodegenerative disease. Currently, there is no cure for HSP but strategies to induce a recovery of spastin levels are emerging as potential therapeutic approaches. Here, we show that MDM2 interacts with spastin MT-interacting and trafficking (MIT) domain. By biochemical and functional experiments, we demonstrate that MDM2 binds spastin and regulates its levels in a post-transcriptional manner independently of the E3 ubiquitin ligase activity. Of relevance, treatment of spastin-deficient cells with the MDM2 inhibitor Nutlin-3a can restore spastin levels and functions, such as cytokinetic abscission and sorting of transferrin receptor. These findings identify MDM2 as a novel interactor of spastin and a potential druggable regulator of its protein levels.